How Playfulness Motivates – Putative Looping Effects of Autonomy and Surprise Revealed by Micro-Phenomenological Investigations - Heimann, Katrin S.; Roepstorff, Andreas (Frontiers in Psychology, 2018)
Play and playfulness have repeatedly been suggested to promote learning and performance, also in environments traditionally not connotated with play. However, finding empirical evidence for these claims has been aggravated by the lack of a definition of play and playfulness fitting to this description. This paper proposes to consider playfulness as an attitude, mode or mental stance, that can be modulated independent of the activity pursued and of the general character of the person. It furthermore introduces the micro-phenomenological method to assess the process and outcome of such modulation. To explore this, we devised a simple building task in a controlled within-subject design, interviewing each participant on how they accomplished the task when asked to perform it so that it either felt playful or not playful. The outcomes of this data driven approach supported this notion of playfulness as a stance, and allowed for specific hypotheses about the temporal course and mechanisms of becoming playful. They suggest that an experience of autonomy and self-expression may be key to the success of the modulation. They furthermore indicate that the resulting playful state may allow for an exploratory engagement with materials that can lead to surprising results. Such unexpected results seem to enhance participants’ feeling of competence which, in turn, may increase the motivation for the task. We discuss these results within the framework of Deci and Ryan´s motivational theory and in relation to current research on gamification and learning.